Antibacterial activity of Mn(i) and Re(i) tricarbonyl complexes conjugated to a bile acid carrier molecule. Issue 10 (28th August 2020) - Betts, Jono W.; Roth, Patrick; Pattrick, Calum A.; Southam, Hannah M.; La Ragione, Roberto M.; Poole, Robert K.; Schatzschneider, Ulrich
Abstract : Mn and Re tricarbonyl bile acid conjugates exhibit low micromolar MIC values and rescue Galleria larvae from bacterial infection. Abstract : A bifunctional cholic acid–bis(2-pyridylmethyl)amine (bpa) ligand featuring an amide linker was coordinated to a manganese(i ) or rhenium(i ) tricarbonyl moiety to give [M(bpa cholamide )(CO)3 ] with M = Mn, Re in good yield and very high purity. Strong antibacterial activity was observed against four strains of methicillin-susceptible (MSSA) and methicillin-resistant (MRSA) Staphylococcus aureus, with minimum inhibitory concentrations (MICs) in the range of 2–3.5 μM. No difference in response was observed for the MSSA vs. MRSA strains. Activity was also independent of the nature of the metal center, as the Mn and Re complexes showed essentially identical MIC values. In contrast to some other metal carbonyl complexes, the activity seems to be unrelated to the release of carbon monoxide, as photoactivation of the Mn complex reduced the potency by a factor of 2–8. Both metal complexes were non-toxic in Galleria mellonella larvae at concentrations of up to 100× the MIC value. In vivo testing in Galleria larvae infected with MRSA/MSSA demonstrated a significant increase in overall survival rates from 46% in the control to 88% in the group treated with the metal complexes. ICP-MS analysis showed that the Mn and Re cholamide complexes are efficiently internalized by E. coli cells and do not interfere with membrane integrity, as evident from a lack of release of intracellular ATP. An increased sensitivity was observed in acrB, acrD, and mdt mutants that are defective in multidrug exporters, indicating that the compounds have an intracellular mechanism of action. Furthermore, E. coli mntP mutants defective in the gene encoding an Mn exporter were more sensitive than the wildtype, while inactivation of the regulator that controls expression of the Mn uptake proteins MntP and MntH slightly increased sensitivity to the compound. Single knockout mutants defective in genes linked to bile salt and oxidative stress response ( dinF, yiaH, sodA, katE, and soxS ) did not show increased sensitivity relative to the wild type. Overall, neither the cholic acid moiety nor the metal-carbonyl fragment alone appear to be responsible for the biological activity observed and thus the search for the primary intracellular target continues.